The HCN1 p.Ser399Pro variant causes epileptic encephalopathy with super-refractory status epilepticus - Yu Kobayashi; Jun Tohyama; Noriyuki Akasaka; Kei Yamada; Moemi Hojo; Eijun Seki; Masaki Miura; Noriko Soma; Takeshi Ono; Mitsuhiro Kato; Mitsuko Nakashima; Hirotomo Saitsu; et al. (Human Genome Variation, 2023)
Abstract HCN1 is one of four genes encoding hyperpolarization-activated cyclic nucleotide-gated channels. The phenotypic spectrum associated with HCN1 variants ranges from neonatal developmental and epileptic encephalopathy to idiopathic generalized epilepsy. We report a Japanese patient with repetitive focal seizures and super-refractory status epilepticus since early infancy caused by a de novo HCN1 variant, NM_021072.4, c.1195T>C, p.(Ser399Pro). This variant might have a dominant-negative effect on channel function, leading to severe epileptic encephalopathy.